Equivalent-linear seismic ground response analysis in Palu area. Issue 1 (December 2021) - Jalil, A; Fathani, T F; Satyarno, I; Wilopo, W
Abstract: The 7.5 Mw Palu earthquake on September 28, 2018, was caused by the Palu Koro fault. This earthquake produced forceful wave propagation in the soil layer and generated enormous surface damage in Balaroa, Petobo, and Jono Oge. Estimations of soil amplification at a specific location are helpful as guidance for infrastructure development. This study examined the effect of local soil in modifying the one-dimensional linear soil response in Balaroa, Petobo, and Jono Oge regions, considering the data of various sites in those regions. The soil response was observed to obtain the synthetic input motion and its effects in the time history of surface acceleration, the ratio of shear stress to effective vertical stress to spectrum response time, and the Fourier amplitude versus frequency ratio. Amplification is standard for ground acceleration, which considers the strong ground motion with the acquired frequency and duration of the content. The results showed that the peak of ground acceleration amplification factors for Balaroa, Petobo, and Jono Oge was around 1.49, 2.05, and 1.27 times, respectively. With a lack of information at the particular site, designers will use the response spectrum obtained along the soil layer to develop earthquake-resistant geotechnical structures in locations close to Palu.